Symposium. Syracuse University: tomo 1 (1946-47), tomo 2 (1948), tomo 3 (1949). - Alatorre, Antonio (Nueva Revista de Filología Hispánica (NRFH), 1958)
Se reseñó: Symposium: tomo 1 (1946-47), tomo 2 (1948), tomo 3 (1949).